STRATEGI PENGGUNAAN MEDIA PEMBELAJARAN E-LEARNING UNTUK MENINGKATKAN HASIL BELAJAR - Moh Fathoni Ali Wafa; Saufal Mardiyah; Agustina Agustina (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
E-learning is a learning method that utilizes information and communication technology, primarily through the internet, to deliver educational content digitally. In e-learning, learners can access study materials, participate in discussions, complete assignments, and communicate with instructors or peers online, without being constrained by time or location. This research aims to understand how e-learning can be effectively implemented, particularly in supporting the needs of digital-native generations who are familiar with technology and the internet. By exploring relevant and engaging methods, approaches, and technological features. This study uses a literature review approach, with data collection techniques drawn from previous research, which are summarized and presented with the latest theories. The e-learning learning strategy is applied through various stages to ensure it is targeted and impactful, ultimately contributing to improvements in students’ academic performance. However, within these strategies, there are risks and challenges that must be continuously evaluated.